virtual social networks in the teaching and learning process of the university student (Revista Electrónica REDINE, 2018)
The purpose of this essay is to reflect on virtual social networks in the teaching and learning process of college level students. Methodologically it was based on the documentary review of some theoretical approaches to argue about the aspects related to social networks that warns of (a) the existence of a network incorporated to the globalized reality; (b) the proximity of cyberspace, in the outline of educational institutions of vocational training; (c) the teaching and learning with the use and use of ICTs and the internet. Finally, it was concluded that virtual social networks should respond to the academic interests of university students and their socializing needs in digital communities, taking advantage of the convergences of telecommunications in the social network through mobile devices, which concentrates the possibilities offered by the ubiquity that transcends distances, time and place in the physical realms of people's communication interaction.
Keywords: virtual social networks; ICT; learning lessons; university student